Changes in the elasticity of fibroadenoma during the menstrual cycle determined by real-time sonoelastography. Issue 6 (June 2015) - Kılıç, Fahrettin; Kayadibi, Yasemin; Kocael, Pinar; Velidedeoglu, Mehmet; Bas, Ahmet; Bakan, Selim; Aydogan, Fatih; Karatas, Adem; Yılmaz, Mehmet Halit
Highlights: We used SWE to evaluate the elasticity of fibroadenomas at different phases of the menstrual cycle, and found significant differences in the premenstrual and postmenstrual stages of the cycle. We propose that one week after menstruation would be appropriate time to perform breast SWE. Evaluations for the postmenstrual phase may reduce the false-positive rates of SWE examinations. Abstract: Objective: Shear-wave elastography (SWE) presents quantitative data that thought to represent intrinsic features of the target tissue. Factors affecting the metabolism of the breast parenchyma as well as age, menstrual cycle, hormone levels, pregnancy and lactation, pre-compression artifact during the examination could affect these elastic intrinsic features. Aim of our study is to determine variation of fibroadenoma elasticity during the menstrual cycle (MC) by means of real-time shear-wave elastography (SWE) and identify the optimal time for SWE evaluation. Methods: Thirty volunteers (aged 20–40 years) who had biopsy-proven fibroadenoma greater than 1 cm in diameter, with regular menstrual cycle and without contraceptive medication underwent SWE (ShearWave on Aixplorer, France) once weekly during MC. Statistical data were processed by using the software Statistical Package for the Social Sciences (SPSS) 19.0. A repeated measures analysis of variance was used for each lesion where the repeated factor was the elastographic measurements (premenstrual, menstrual and postmenstrual). Pillai's trace test was used. Pairwise correlation was calculated using Bonferroni correction. Values of p  < 0.05 were considered statistically significant. Results: The mean elasticity value of fibroadenomas in mid-cycle was 28.49 ± 12.92 kPa, with the highest value obtained in the third week corresponding to the premenstrual stage (32.98 ± 13.35 kPa) and the lowest value obtained in the first week corresponding to the postmenstrual stage (25.39 ± 10.21 kPa). Differences between the elasticity values of fibroadenomas in premenstrual and postmenstrual periods were statistically significant ( p  < 0.001). There were no significant differences in lesion size between the different phases of the menstrual cycle ( p  > 0.05). Conclusion: In this study, we found that there is significant difference between the elasticity values of fibroadenomas on premenstrual and postmenstrual period. We propose that one week after menstruation would be appropriate time to perform breast SWE.